2021
DOI: 10.1002/anie.202114238
|View full text |Cite
|
Sign up to set email alerts
|

A Reconstructed Cu2P2O7 Catalyst for Selective CO2 Electroreduction to Multicarbon Products

Abstract: The electrochemical CO 2 reduction reaction (CO 2 RR) over Cu-based catalysts shows great potential for converting CO 2 into multicarbon (C 2 + ) fuels and chemicals. Herein, we introduce an A 2 M 2 O 7 structure into a Cu-based catalyst through a solid-state reaction synthesis method. The Cu 2 P 2 O 7 catalyst is electrochemically reduced to metallic Cu with a significant structure evolution from grain aggregates to highly porous structure under CO 2 RR conditions. The reconstructed Cu 2 P 2 O 7 catalyst achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(56 citation statements)
references
References 40 publications
(23 reference statements)
4
52
0
Order By: Relevance
“…3a ). The trade-off relationship was reported in previous studies, which can be ascribed to the electrochemical conversion of CO to C 2+ products 33 , 34 . Overall, these experimental results clearly suggest that the K + cation can suppress the competing HER and promote C 2+ production simultaneously over ER-CuNS catalyst in strongly acidic electrolyte.…”
Section: Resultssupporting
confidence: 65%
“…3a ). The trade-off relationship was reported in previous studies, which can be ascribed to the electrochemical conversion of CO to C 2+ products 33 , 34 . Overall, these experimental results clearly suggest that the K + cation can suppress the competing HER and promote C 2+ production simultaneously over ER-CuNS catalyst in strongly acidic electrolyte.…”
Section: Resultssupporting
confidence: 65%
“…Hence, a sol‐gel method was utilized to synthesize Zn 2 P 2 O 7 pre‐catalysts for CO 2 RR, which was reduced to the nonstoichiometric ZnO x demonstrated by both operando characterization techniques and theoretical simulation [48] . The similar pre‐catalyst of Cu 2 P 2 O 7 was also reported for CO 2 RR [90] . Besides this, Tian et al [91] .…”
Section: Stability Of Catalysts Containing Pvmssupporting
confidence: 68%
“…[48] The similar pre-catalyst of Cu 2 P 2 O 7 was also reported for CO 2 RR. [90] Besides this, Tian et al [91] reported that the introduction of Sn/In 2 O 3 interlayer to Cu 2 O pre-catalyst system to form CuInO 2 nanoparticles, which was beneficial to keep positive state Cu(I) good catalytic stability; the obtained CuInO 2 nanoparticles exhibit a dramatically higher activity during the CO 2 RR at a relatively lower overpotential compared with the traditional Cu nanoparticles derived from common Cu 2 O. Nevertheless, after the in situ evolution of precatalysts during CO 2 RR, the identification of the corresponding real local activity structure is always sluggish and still difficult to be identified even by the advanced experimental characterization technologies.…”
Section: Stability Of Catalysts Containing Pvmsmentioning
confidence: 99%
“…Considering the well-recognized reconstruction behavior of Cu-based catalysts under CO 2 RR conditions, [9,23] we conducted a series of physicochemical characterizations after CO 2 RR. XRD patterns show that both CuO x @C and CuO x catalysts undergo composition change from CuO species to the mixture of Cu 2 O and metallic Cu (Figure 2a).…”
mentioning
confidence: 99%
“…[11] It is reported that Cu + species can promote the CÀ C coupling step, [19][20][21] however, Cu-based materials, especially Cu-based oxides, are inevitable to be electrochemically reduced under the negative potential during CO 2 RR. [22,23] The other one is that stabilizing and tuning the key intermediate (*HOCCH) goes the hydrogenation pathway of *HOCCH to *HOCHCH (ethanol pathway) instead of dehydroxylation way of *HOCCH to *CCH (ethylene pathway) in the bifurcation, which is critical to determine the Faradaic efficiency of ethanol and ethylene. [3,24] Recently, Xia et al report that carbon confinement can suppress the reduction of metal oxides and maintain high valence state of active sites.…”
mentioning
confidence: 99%